EPIGRAPHIC DISKS AND HORSEMEN RELIEFS ON THE STELAS FROM THE FAMILY CEMETERY OF KAITAG RULERS - Musaev, Mahac Abdulaevic; Sihaliev, Samil' Sihalievic; Sehmagomedov, Magomed Gadzievic (History, Archeology and Ethnography of the Caucasus, 2019)
The paper presents some of the study results of the family cemetery of hereditary rulers of Kaitag, located in Qala-Quraysh. During several expeditions in 2017–2018, more than 40 stelas, dating XIV c. – 1803/04, were studied. Names of the deceased, dates of their death, and other historical information, as well as poems, religious sayings, prayers and Quran Ayat in Arabic are inscribed on them. The stelas are made with high craftsmanship, distinguished by the refinement of the ornament and the elegance of epigraphic ribbons. Each stela of the necropolis can be described as a work of art. Among other interesting finds there are ten epigraphic disks on the stelas of the XVI–XVIII c. They are carved on the backsides of the monuments, have common composition, ornament, and similar contents: prayers to Allah for mercy on Judgment day. The article also describes horsemen relief images on two stelas of the early XVIII c., as well as a false horseman, carved on the tombstone of the late XVI c. Compositional decision of the relief is such that the weapons and armor are located above the horse, creating an effect of the rider’s presence, although the rider himself is not there. If the image weren’t stained, it would be impossible to reveal that it is not a horseman. The effect of presence is achieved by different artistic techniques. Among them is the image of a moving horse.The introduction of stated elements of tombstone decoration into scientific circulation contributes to dating of monuments with identical decor, and revealing interregional connections in stone carving craft.
Keywords: Arabic epigraphy; Qala-Quraysh; Kaitag; stone reliefs; necropolistics.